Process Optimization for Biodiesel Production from Corn Oil and Its Oxidative Stability - N. El Boulifi; A. Bouaid; M. Martinez; J. Aracil (International Journal of Chemical Engineering)
Response surface methodology (RSM) based on central composite design (CCD) was used to optimize biodiesel production process from corn oil. The process variables, temperature and catalyst concentration were found to have significant influence on biodiesel yield. The optimum combination derived via RSM for high corn oil methyl ester yield (99.48%) was found to be 1.18% wt catalyst concentration at a reaction temperature of 55.6∘C. To determine how long biodiesel can safely be stored, it is desirable to have a measurement for the stability of the biodiesel against such oxidation. Storage time and oxygen availability have been considered as possible factors influencing oxidative instability. Biodiesel from corn oil was stored for a period of 30 months, and the physico-chemical parameters of samples were measured at regular interval of time. Results show that the acid value (AV), peroxide value (PV), and viscosity (ν) increased while the iodine value (IV) decreased. These parameters changed very significantly when the sample was stored under normal oxygen atmosphere. However, the ν, AV, and IV of the biodiesel sample which was stored under argon atmosphere were within the limit by the European specifications (EN 14214).